Measurement of W + - boson production in Pb+Pb collisions at √sNN=5.02 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (The European physical journal. C, Particles and fields, 2019)
A measurement of $$W^± $$W± boson production in Pb+Pb collisions at $$\sqrt{s_NN} = 5.02~\text {Te}\text {V}$$sNN=5.02Te is reported using data recorded by the ATLAS experiment at the LHC in 2015, corresponding to a total integrated luminosity of $$0.49\;\mathrm {nb^{-1}}$$0.49nb-1. The $$W^± $$W± bosons are reconstructed in the electron or muon leptonic decay channels. Production yields of leptonically decaying $$W^± $$W± bosons, normalised by the total number of minimum-bias events and the nuclear thickness function, are measured within a fiducial region defined by the detector acceptance and the main kinematic requirements. These normalised yields are measured separately for $$W^+$$W+ and $$W^-$$W- bosons, and are presented as a function of the absolute value of pseudorapidity of the charged lepton and of the collision centrality. The lepton charge asymmetry is also measured as a function of the absolute value of lepton pseudorapidity. In addition, nuclear modification factors are calculated using the $$W^± $$W± boson production cross-sections measured in pp collisions. The results are compared with predictions based on next-to-leading-order calculations with CT14 parton distribution functions as well as with predictions obtained with the EPPS16 and nCTEQ15 nuclear parton distribution functions. No dependence of normalised production yields on centrality and a good agreement with predictions are observed for mid-central and central collisions. For peripheral collisions, the data agree with predictions within 1.7 (0.9) standard deviations for $$W^-$$W- ($$W^+$$W+) bosons.